Painting by Andrew P. Hill - Gordon, John C. (photographer):::Creator::::::::::::; Hill, Andrew Putnam, 1853-1922 (painter):::Contributor::::::::::::
Photograph of a painting by Andrew P. Hill. The scene depicts a field where cows roam and people ride on horseback. The artist's name and 1909 are written on the lower left of the painting. Written in ink on the verso of the photograph: "Andrew P. Hill, 1909."